Production of oriented strand board (OSB) from Eucalyptus benthamii and Pinus spp wood at different layer combination Produção de painéis de partículas orientadas (OSB) de Eucalyptus benthamii e Pinus spp. em diferentes combinações de camadas - Gorski L.* (2015)
The aim of this study was to evaluate the oriented strand board (OSB) of Eucalyptus benthamii and Pinus spp. for physical and mechanical properties. The particles were obtained from 13 years old Eucalyptus logs and particles of Pinus spp were from industrial process, being composed of the mix of particles of Pinus taeda and Pinus elliottii. The experiment involved 5 treatment composed of 3 layers of particles in the mat, arranged perpendicular to each other in the ratio 20:60:20, namely: only particles of Eucalyptus (T1), only Pinus (T2), Eucalyptus:Pinus:Eucalyptus (T3), Pinus:Eucalyptus:Pinus (T4) and Pinus+Eucalyptus mixed in each of the layers (T5). The panels were produced with a density of 0.65 g/cm', 6% phenol formaldehyde resin, 1% paraffin emulsion pressing cycle and 180°C, 40 kgf/cm' for 8 minutes. The assays were performed according to ASTM (2002) and DIN (1982). The analysis of variance and the Scott-Knott test at 95% probability was used, and the comparison of the CSA standard(1993). The results showed that the panels of T1 had the best results for water absorption, thickness swelling and spring-back, but the results were not satisfactory when compared with the reference standard. For mechanical properties, in general, the best results were obtained in treatment T2 with 100% Pinus particles.